PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MEMPERBAIKI PROSES PEMBELAJARAN DAN MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS VIIIE SMP NEGERI 18 PEKANBARU - Istiqoidah, Anita; Solfitri, Titi; Siregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the lower result of students’ mathematic learning at class VIIIE of SMPN 18 Pekanbaru, which shows that only about 15,78% of students achieving KKM standard for algebra. This research aims to improve the learning process and students’ mathematic learning outcomes by implementing cooperative learning model TSTS type. This is a classroom action research with two cycles. The subjects of this research were class VIIIE of SMPN 18 Pekanbaru on odd semester academic year 2017/2018 which consits of 17 girls and 21 boys. The instrument of the data collector on this research are observation sheets and the test results of mathematic learning. The observation sheets were analyzed qualitatively to see the learning activities which had not maximize, in order to structured the improvement in second cycle, and for the test results were analyzed quantitatively. From the qualitative analization of this research, has known that there is an improvement of the mathematic learning activities for each meetings, since the first day of first cycle to the last day of second cycle. The research also shows the result of students’ mathematic learning based on individual development scors from first quiz to second quiz, where the students who get 20 and 30 are more than the students who get 5 and 10. The analysis of KKM standard achievement also shows an increasing of mathematic learning outcomes, which the percentage of basic score is 15,78%, the percentage of first quiz is 44,73%, and the percentage of second quiz is 57,89%. The conclusion of these result analysis is that the implementation of cooperative learning model Two Stay Two Stray (TSTS) type can improve the learning process and mathematic learning outcomes at class VIIIE of SMPN 18 Pekanbaru on odd semester academic year 2017/2018.Keywords: Mathematics Learning Outcomes, Cooperative Learning, Two stay Two stray, Classroom Action Research